Texture Surface Analysis of Hydrodynamic Journal Bearing - Yang, Chong Yew (IRC, 2016)
Journal bearing is one of the mostly used types of bearing in rotating machinery. However, it has been a big concern on its performance in terms of load capacity which leads to failure. Texture and groove are two of the proven ways to improve its load capacity and performance but the question is which configurations is optimum to apply the texture and groove. In past study, there were no records on the uses of the 2 steps grooves design on the bearing. Thus in this study, the model of interest would be the bearing configuration with 2 steps groove and the objective is to investigate the effect of texturing and grooving on the load capacity using the selected configuration. The study is conducted using the Modified Reynolds Equation and Matlab programming to mathematically solve for the load capacity of the bearing. 2 models will be used which are 1 step grooves bearing as the benchmark and the main model would be the 2 steps grooves bearing. From the results, it seen that 2 steps groove bearing is less effective compared with 1 step groove bearing where it yields lower load capacity as the bearing operates. The project is limited by the simplified equation used where several more parameters were not considered and the validation is done by comparing with past research findings. It is suggested that study can be done using CFD modelling in order to validate the results between 2 approaches.